Analysis of Factors Affecting Consumer Satisfaction Using SEM (Structural Equation Modeling) Method - Much Djunaidi; Ranis Duanda Gunari (OPSI, 2022)
The era of globalization in Indonesia in the business sector has experienced very rapid development. This is because the number of consumptive age or millennial generation in Indonesia is increasing every year. This very rapid business development provides an opportunity to set up independent businesses for entrepreneurs. One of the many independent businesses established is a coffee shop. One of the independent businesses engaged in the coffee shop is Ueno Coffee. The rapid development of the coffee shop business has resulted in increasingly fierce competition between competitors so that coffee shop entrepreneurs make it a threat and a challenge. With these threats and challenges, Ueno Coffee wants to conduct a customer satisfaction analysis that can be used to evaluate customer satisfaction so that it can be used for business development that is better, superior and able to compete with competitors. This study using the SEM-PLS method is expected to be able to assist business owners in analyzing the factors that effect consumer satisfaction. This study applies a simple random sampling technique with a sample of 100 people. The results of the analysis show that the variables of product quality, service quality, price, promotion, location and halal label have a positive value and have a significant effect on Ueno Coffee's consumer satisfaction.